Decolorization of Melanoidin Using Sono–Fenton and Photo–Fenton Processes - Apichon Watcharenwong; Kawintra Kongka; Anusara Kaeokan; Chanat Chokejaroenrat; Chainarong Sakulthaew (Waste, 2023)
Ethanol production wastewater contains high quantities of dark–brown pigments (melanoidin) that result in low color removal using conventional biological treatments. Advanced oxidation processes (AOPs) are the most documented methods for reducing the color associated with melanoidin. This study examines the degradation of melanoidin using AOPs based on photo–Fenton, sono–Fenton, and sono–photo–Fenton processes. Their effects on decolorization were investigated based on light intensity, ultrasonic frequency, and the iron concentration (Fe2+)–to–H2O2 ratio. This study showed that ultrasonic waves and UV light result in a higher melanoidin decolorization efficiency than Fenton reactions alone. The initial color values were reduced from 5000–5500 ADMI to below 500 ADMI for both processes because the ultrasonic waves and ultraviolet light induced H2O2 breakdown into the 🞄OH radical. Reducing the color of the melanoidin using the photo–Fenton process resulted in a decolorization rate of 0.1126 min−1, which was higher than the rates of both the sono–Fenton and sono–photo–Fenton processes. These results provide proof that the photo–assisted Fenton process is more applicable to treating dye–contaminated water than are other enhancing approaches.